Safety of the hospital environment - CIOBANU, Elena (One Health & Risk Management, 2021)
Introduction. Prophylaxis and control of infections is a priority issue of the global health system. According to the World Health Organization, the role of infection prevention in the field of hospital safety and the quality of the medical record is important, both for medical workers and patients. "Modern scientific research in the field of infection prevention and control shows that none of the medical institutions in any country can claim to be outside the risk of infections associated with the provision of medical care" (WHO). According to data from the European Center for Disease Prevention and Control, more than 4.1 million people in the European Union annually have an infection associated with healthcare, and about 37 thousand die as a result of this infection. Material and methods. The analysis was performed based on the information and statistical data provided by the annual reports of the National Agency for Public Health of the Republic of Moldova, during the years 1993-2017. The study is retrospective. Results. The safety of the hospital environment is in a causal interrelation with the healthcare-associated infections which represents a medical, social and economic problem, determined by the increased frequency of these infections even in well-equipped hospitals. Thus, a safe hospital environment – is a cumulative term that includes both protection from infections, as well as conditions of compliance with the rules of personal hygiene, curative-protective regime, psychological protection of patients and medical personnel. Official statistics in the Republic of Moldova do not reflect the actual morbidity through infections associated with healthcare and consequently, underestimate their importance. The dynamics of morbidity through these infections in the Republic of Moldova (1993-2017) is uneven, with an increase in incidence in recent years. In 2017, 1156 cases of infections were reported in the country (in 2016 – 1114 cases), which is about 2.0 cases per 1000 hospitalized patients. The structure of infections associated with healthcare in recent years has not undergone essential changes regarding the placement of nosological forms, placing first the infections in the cases with 9.9 (2016 – 9.6) cases per 1000 births, followed by neonatal infections – 2.9 cases per 1000 surgeries (2016 – 2.2), surgical wound infections – 1.5 cases per 1000 surgeries (2016 – 1.5), followed by consecutive infections of therapeutic injections, ventilator-associated pneumonia, infections during the perinatal period and urinary tract infections. Conclusions. In order to combat and prevent healthcare-associated infections, the actual prevalence of which is not known, a program of infection surveillance and training of medical personnel must be implemented, which will contribute to the increase of the safety of the hospital environment, for both patients and medical personnel.